From Local to Global: How Community-Based Climate Action Shapes International Environmental Diplomacy (American Journal of Public Diplomacy and International Studies (2993-2157), 2025)
The global climate governance is also characterized by an intention-action gap accompanied by North-South equity issues and technology-transfer tensions. This study explores the way community-based climate action may fill that gap. Adopting an interpretivist, qualitative design, three cases of MENA (Jordanian water conservation, Moroccan reforestation, Saudi urban flood resilience) were examined through document analysis, semi-structured interviews, and secondary climate data using thematic analysis. The data and national references were updated and analyzed according to the Fourth National Communication (2023), Second Biennial Update Report (2021) and Updated Nationally Determined Contribution (2021) of Jordan, in accordance with the policy of the National Climate Change 20202050 and the National Adaptation Plan (2021). Findings indicate that grassroots efforts percolate up through the effects of demonstrations, signifying national policy tools and contributing to the viability and credibility of the NDCs; and also, they serve as diplomatic capital that actualizes equity, enhances North-South collaboration and improves trustworthiness in submissions to the UNFCCC. Recommendations include the institutionalization of local-global knowledge platforms, the focus of finance on community-led adaptation, and the involvement of community actors in the process of delegation negotiation. The paper also highlights the increasing importance of community-based climate diplomacy as an example of the Al-Munther Al-Monakhi Initiative that was initiated by the author at COP29. The initiative shows how the involvement of the bottom-up can support national policies and fill the gap between global pledges and local action through translation of the principles of the Paris Agreement and the Updated NDCs of Jordan into activities and opportunities that are accessible and community-based. Implications reposition environmental diplomacy as multi-scalar, enhancing the ambition, fairness and implementation.